KULTURA SZKOŁY W ROZUMIENIU DESKRYPTYWNYM I NORMATYWNYM. WYBRANE EGZYMPLIFIKACJE - Nowosad, Inetta (Rocznik Pedagogiczny, 2018)
The article addresses the ambiguity in understanding school culture and its potential research im- plications. The analyses were embedded within two key approaches: normative and descriptive, illustrating selected exemplifications of theoretical positions of school culture in German-speaking countries. Also, the potential for integration of both approaches into a new model of school culture was proposed by La Tefy Schoen and Charles Teddi in 2008, which terminated the separation be- tween descriptive and normative approaches to school culture.